2017
DOI: 10.1002/ijc.30772
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of selected nutrients and persistence of HPV infection in men

Abstract: Human papillomavirus (HPV) infection is a common sexually transmitted disease. Although often transitory, persistent oncogenic HPV infection may progress to a precursor lesion and, if not treated, can further increase the risk of cancer. The purpose of this study was to investigate the relation between dietary intake and HPV persistent infection in men of a Brazilian cohort. The study population consisted of 1,248 men from the Brazilian cohort of the HIM (HPV in Men) Study, ages 18 to 70 years, who completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 31 publications
(101 reference statements)
2
20
0
Order By: Relevance
“…For entering the 24‐hour recall data in the NDSR software, the standardized methodological for dietary intake assessment was used. Several studies that evaluated food intake in Brazil have used NDSR to assess dietary intake To adjust dietary intake for intra‐and‐interpersonal variability with the intention to reduce information bias (adjusting variability for day of the week, sex, age, mother's education, BMI, and per capita income) and to estimate individual's usual food intake, it was used the method developed by the Iowa State University . Moreover, all nutrients were adjusted for total energy .…”
Section: Exposurementioning
confidence: 99%
“…For entering the 24‐hour recall data in the NDSR software, the standardized methodological for dietary intake assessment was used. Several studies that evaluated food intake in Brazil have used NDSR to assess dietary intake To adjust dietary intake for intra‐and‐interpersonal variability with the intention to reduce information bias (adjusting variability for day of the week, sex, age, mother's education, BMI, and per capita income) and to estimate individual's usual food intake, it was used the method developed by the Iowa State University . Moreover, all nutrients were adjusted for total energy .…”
Section: Exposurementioning
confidence: 99%
“…Deficiencies of carotenoids such as vitamin A are clearly associated with the onset of cervical cancer and its precursor lesions, and folate deficiencies are related to the occurrence of pre-cancerous lesions of the cervix [17]. In a study conducted on 1,248 men with HPV infection, it was observed that patients who consumed more retinol, vitamin A and folates had a lower persistence of HPV infections [16]. Folates could play a role in regulating the integration and stability of the viral genome, thanks to its involvement in DNA synthesis, repair and methylation [15,29].…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, HPVs can be classified as low risk (LR-HPV) or high-risk viruses (HR-HPV), depending on the risk of developing cancer by their infection persistence [2]. In this sense, fifteen HPV types are considered high-risk types (16,18,31,33,35,39,45,51,52,56,58,59,68,73, and 82) while 3 are classified as probable high-risk types (26,53, and 66) [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations